MicroRNA-661, a c/EBPα Target, Inhibits Metastatic Tumor Antigen 1 and Regulates Its Functions - Reddy, Sirigiri Divijendra Natha; Pakala, Suresh B.; Ohshiro, Kazufumi; Rayala, Suresh K.; Kumar, Rakesh (Cancer research (Chicago, Ill.), 2009)
MicroRNAs (miR) have been identified as posttranscriptional modifiers of target gene regulation and control the expression of gene products important in cancer progression. Here, we show that miR-661 inhibits the expression of metastatic tumor antigen 1 (MTA1), a widely up-regulated gene product in human cancer, by targeting the 3′ untranslated region (UTR) of MTA1 mRNA. We found that endogenous miR-661 expression was positively regulated by the c/EBPα transcription factor, which is down-regulated during cancer progression. c/EBPα directly interacted with the miR-661 chromatin and bound to miR-661 putative promoter that contains a c/EBPα-consensus motif. In addition, we found that the level of MTA1 protein was progressively up-regulated, whereas that of miR-661 and its activator, c/EBPα, were down-regulated in a breast cancer progression model consisting of MCF-10A cell lines whose phenotypes ranged from noninvasive to highly invasive. c/EBPα expression in breast cancer cells resulted in increased miR-661 expression and reduced MTA1 3′UTR-luciferase activity and MTA1 protein level. We also provide evidence that the introduction of miR-661 inhibited the motility, invasiveness, anchorage-independent growth, and tumorigenicity of invasive breast cancer cells. We believe our findings show for the first time that c/EBPα regulates the level of miR-661 and in turn modifies the functions of the miR661-MTA1 pathway in human cancer cells. Based on these findings, we suggest that miR-661 be further investigated for therapeutic use in down-regulating the expression of MTA1 in cancer cells. [Cancer Res 2009;69(14):5639–42]